A REVIEW OF CYCLODESTRUCTIVE SURGICAL PROCEDURES FOR THE TREATMENT OF VARIOUS TYPES OF GLAUCOMA - F. FURKATZOD; KH.J. KARIM-ZADE; SH.K. MAKHMADZODA (Avicenna Tajik State Medical University, 2021)
Glaucoma remains a significant problem in ophthalmology. It is characterised by increased intraocular pressure (IOP), visual field loss, and optic nerve degeneration. Despite some progress achieved in the diagnosis and treatment of the disease, millions still suffer from glaucoma (currently, according to WHO, there are more than 106 million people globally), and many patients are already in the later stages. The accompanying pain syndrome sometimes forces doctors to remove the eye. In this regard, several so-called organ-preserving operations were introduced, the purpose of which is to reduce the production of intraocular fluid (IOF) and, accordingly, eliminate the pain syndrome. Glaucoma treatment includes conservative and surgical interventions. Surgical methods for glaucoma treatment aim to improve the outflow of intraocular fluid (fistulising operations) or reduce its production (cyclodestructive procedures). This paper analyses the evolution of surgical interventions to reduce intraocular fluid production by destroying the aqueous humour-producing ciliary processes. Systematic review searches were performed using Google Scholar, Pubmed, Web of Science, Cyberleninka, and Cochrane Library databases for articles published up to 2020 using keywords related to cyclodestruction (CD), cyclophotocoagulation (CPC), and treatment of refractory glaucoma (RG).